Residue hydroprocessing catalyst, preparation and use thereof
Patent Information
- Application Number
- CN202510570126.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-30
AI Technical Summary
当前,普通氧化铝酸性较为单一、负载金属时与活性组分间的作用太强,导致深度加氢的目的还不能很好的实现
[0065]本发明提供了一种渣油加氢催化剂的制备方法,首先,采用自组装法,主要通过控制醇/铝摩尔比、醇/模板剂摩尔比以及模板剂的引入方式,同时在自组装的过程中引入双功能结构导向剂,结合水热处理,制备比表面积、孔结构和表面酸分布更加适宜的介孔氧化铝;然后,以上述介孔氧化铝材料为基础,将其与具备大孔的高温型活性炭以及部分主活性金属(第VIB族金属)混合成型,得到的加氢催化剂中间体具有更加适宜的孔分布以及B酸酸分布,为后续“内水相/油相/外水相”型多相浸渍液负载提供基础,通过各步骤综合协调,所得催化剂用于渣油加氢脱金属反应中,脱金属活性性能以及长周期运转性能显著提升。
Smart Images

Figure BDA0005386951510000131 
Figure BDA0005386951510000132 
Figure BDA0005386951510000133
Abstract
Description
Technical Field
[0001] This invention relates to a hydrogenation catalyst, specifically to a residue oil hydrogenation catalyst and its preparation and application. Background Technology
[0002] With the increasing trend of heavier and lower-quality crude oil worldwide, heavy oil hydrotreating technology plays an increasingly important role in the efficient utilization and lightening of crude oil. Alumina, as the main carrier of hydrotreating catalysts, possesses characteristics such as a large specific surface area, excellent pore structure, a certain acid strength distribution, and high hydrothermal and thermal stability, playing a crucial role in the hydrotreating process. Currently, ordinary alumina has relatively simple acidity, and the interaction between loaded metals and active components is too strong, preventing the full realization of deep hydrotreating goals. Especially in the hydrotreating of heavy oil, the small pore size of ordinary alumina restricts the diffusion of large molecules during the reaction, making the catalyst more prone to deactivation, and the utilization rate of active metals needs further improvement.
[0003] CN103539173A discloses a method for preparing a highly thermally stable ordered mesoporous alumina material. This material maintains good pore order after calcination at 1000℃ for 1 hour. It uses inorganic aluminum sources such as aluminum nitrate and aluminum chloride as raw materials, P123 as a template agent, and organic carboxylic acids as surface protectants in ethanol and aqueous solutions. The ordered mesoporous alumina material is synthesized through solvent evaporation-induced self-assembly. The pore size of this material is 4.0–10.0 nm, and the specific surface area is 200–400 m². 2 / g, pore volume 0.3~1.0cm³ 3 / g.
[0004] Currently, there are many ways to synthesize alumina, but how to prepare alumina-based support materials with better overall performance, and on the basis of the above, prepare hydrogenation catalysts with excellent performance, is an important research direction. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a residue oil hydrotreating catalyst, its preparation, and its application. When used in the residue oil hydrotreating demetallization reaction, the catalyst exhibits significantly enhanced demetallization activity, ensuring long-term stable operation of the equipment.
[0006] The first aspect of this invention provides a method for preparing a residue oil hydrotreating catalyst, comprising the following steps:
[0007] (0) Preparation of an impregnation solution containing a second active metal:
[0008] First, the inner aqueous phase containing the second active metal is added dropwise to the oil phase to obtain an "inner aqueous phase / oil phase" type emulsion; then it is added dropwise to the outer aqueous phase to obtain an impregnation solution containing the second active metal, namely an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution.
[0009] (1) Aluminum sol A, alcoholic solution of template agent B and mixture X containing bifunctional structure directing agent are mixed, subjected to hydrothermal treatment, dried and calcined to obtain mesoporous alumina;
[0010] (2) The mesoporous alumina, activated carbon, first active metal source and molding aid obtained in step (1) are mixed and shaped, dried and calcined to obtain a catalyst intermediate;
[0011] (3) Impregnate the catalyst intermediate obtained in step (2) with an impregnation solution containing a second active metal, dry and calcine to obtain the catalyst.
[0012] Further, in step (1), the preparation process of aluminum sol A is as follows: aluminum source, acid and alcohol are mixed and pre-hydrolyzed to obtain aluminum sol A. Further, the alcohol / aluminum molar ratio is 10.0 to 80.0, preferably 10.0 to 45.0. The acid / aluminum molar ratio is 1.0 to 12.0, preferably 1.0 to 5.0.
[0013] Furthermore, the pre-hydrolysis is carried out under stirring conditions, and the stirring rate is not particularly limited. The pre-hydrolysis temperature is 20–60°C, and the pre-hydrolysis time is 1–12 hours. Furthermore, the aluminum source is one or more of aluminum sources such as aluminum nitrate, aluminum chloride, and aluminum isopropoxide. The acid is an inorganic acid, preferably one or more of sulfuric acid, nitric acid, and hydrochloric acid. The alcohol is a low-carbon alcohol, preferably one or more of ethanol, propanol, and butanol.
[0014] Further, preferably, in step (1), the preparation process of aluminum sol A is as follows: first, aluminum source, acid and alcohol are mixed and pre-hydrolyzed to obtain a precursor solution; then, an ionic emulsifier is added dropwise to the precursor solution to obtain aluminum sol A. The amount of ionic emulsifier added is related to the amount of precursor solution used in a relationship of 0–18 g / 100 mL, preferably 5–15 g / 100 mL.
[0015] Furthermore, the ionic emulsifier is one or more of anionic emulsifiers such as sodium dodecyl sulfate and fatty polyoxyethylene ether sulfate salt (chemical structure formula RO(CH2CH2O)n-SO3Na (n=1~15, R is a fatty alkyl group of C10~C22)).
[0016] Further, in the alcohol solution B of the template agent, the alcohol is one or more low-carbon organic alcohols such as ethanol, propanol, and butanol. The template agent is at least one of P123 (polyethylene glycol-polypropylene glycol-polyethylene glycol triblock copolymer), SDBS (sodium dodecylbenzenesulfonate), and AOT (dioctyl sulfosuccinic acid), preferably P123. The molar ratio of alcohol to template agent is 300–1000.
[0017] Further, in step (1), the molar ratio of aluminum source to template agent in aluminum sol A is 50–200, for example, but not limited to, 50, 60, 70, 80, 90, 100, 120, 140, 160, 180, 200, etc. Further, after mixing, the mixture is stirred at 20–60°C for 1–6 hours, and the stirring rate is not particularly limited.
[0018] Further, in step (1), the mixture X containing the bifunctional structure directing agent includes the bifunctional structure directing agent, an alcohol, and an acid, wherein the alcohol is preferably ethanol, and the acid is preferably nitric acid; the bifunctional structure directing agent is polyethylene glycol-distearatephosphatidylethanolamine (molecular weight of 500-5000).
[0019] Further, in step (3), the volume ratio of alcohol to acid in the mixture X is 4 to 12. In the mixture X, the ratio of the mass of the bifunctional directed agent to the sum of the volumes of alcohol and acid is 0.05 to 0.85 g / mL, preferably 0.30 to 0.75 g / mL.
[0020] Further, in step (1), the ratio of the molar amount of the bifunctional structure directing agent to the sum of the molar amounts of the bifunctional structure directing agent and the aluminum source in aluminum sol A is 0.1 to 0.5.
[0021] Preferably, in step (1), aluminum sol A is first added dropwise to the alcohol solution B of the template agent to obtain solution C; then, the mixture X containing the bifunctional structure directing agent is added dropwise to solution C for hydrothermal treatment. Further, the conditions for the hydrothermal treatment are: temperature 160-280℃, preferably 180-260℃, time 3-12h, preferably 4-8h.
[0022] Further, in step (1), after the hydrothermal treatment, the solution is first cooled to room temperature (20-30°C) to obtain solution D, which is then dried and calcined to obtain mesoporous alumina. The drying temperature is 120-200°C, and the drying time is 4-10 hours. The calcination temperature is 500-650°C, and the calcination time is 3-8 hours.
[0023] Further, in step (2), the activated carbon is a high-temperature activated carbon, with a minimum heat resistance temperature of not less than 700℃, preferably 720~800℃. The activated carbon has a pore volume of 1.0~1.8mL / g, and the pore volume with a pore size of 50.0~300.0nm accounts for 15%~35% of the total pore volume.
[0024] Further, in step (2), the molding aid is one or more of guar gum powder, methylcellulose, etc. The molding method can be at least one of extrusion, sheeting, and ball rolling. The shaped product can be clover-shaped, four-leaf clover-shaped, butterfly-shaped, cylindrical, spherical, or strip-shaped, etc.
[0025] Further, in step (2), the mass of the molding aid added is 1.0% to 8.0% of the total mass of mesoporous alumina and activated carbon.
[0026] Further, in step (2), the first active metal is one or more group VIB metals, preferably Mo and / or W; further, the molybdenum source is selected from at least one of ammonium heptamolybdate, ammonium tetramolybdate, molybdenum oxide, etc., and the tungsten source is ammonium metatungstate. The mass (based on oxides) of the first active metal source is 8% to 18% of the total mass of mesoporous alumina and activated carbon.
[0027] Further, in step (2), the drying temperature is 120–200°C, and the drying time is 4–10 h. The calcination temperature is 500–650°C, and the calcination time is 3–8 h.
[0028] Further, in step (3), the second active metal includes a Group VIB metal and a Group VIII metal, wherein the Group VIII metal is preferably Ni and / or Co, and the Group VIB metal is preferably Mo and / or W. The Group VIB metal source is one or more of ammonium tetramolybdate, ammonium heptamolybdate, molybdenum oxide, ammonium metatungstate, etc., and the Group VIII metal source is one or more of basic nickel nitrate, cobalt nitrate, etc.
[0029] Further, in step (3), the impregnation is preferably saturated impregnation. After impregnation, the catalyst is obtained by conventional filtration and washing, drying, and calcination. The drying temperature is 120–200°C, and the drying time is 4–10 h. The calcination temperature is 500–650°C, and the calcination time is 3–8 h.
[0030] Furthermore, the method for preparing the impregnation solution containing the second active metal includes:
[0031] (a) Mix the co-emulsifier, the VIB metal source, water, and optional auxiliary source, and heat to obtain a clear solution;
[0032] (b) The group VIII active metal source, the water-soluble polymer, and the clear solution obtained in step (a) are mixed to obtain the internal aqueous phase;
[0033] (c) The aqueous phase from step (b) is added dropwise to the oil phase to obtain an "aqueous phase / oil phase" emulsion;
[0034] (d) Mix the hydrophilic agent and water to obtain the external aqueous phase;
[0035] (e) The “inner aqueous phase / oil phase” type emulsion obtained in step (c) is added dropwise to the outer aqueous phase obtained in step (d) to obtain an impregnation solution containing the second active metal, namely the “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0036] Further, in step (a), the co-emulsifier is selected from one or more of polyethylene glycol-8000, polyethylene glycol-400, cetyl alcohol, octadecanol, propylene glycol, n-butanol, polyvinyl alcohol, and glycerin.
[0037] Further, in step (a), the amount of the co-emulsifier is 0.5% to 5.0% of the mass of the internal aqueous phase obtained in step (b).
[0038] Further, in step (a), the Group VIB metal is Mo and / or W, the molybdenum source can be one or more of molybdenum oxide, ammonium tetramolybdate, ammonium heptamolybdate, etc., and the tungsten source can be ammonium metatungstate. The auxiliary agent is selected from at least one of phosphorus, silicon, or boron, preferably phosphorus; the phosphorus source can be one or more of phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, etc.
[0039] Further, in step (a), the water is distilled water or deionized water, and the conductivity of the water should be less than 10.0 mS.
[0040] Further, in step (a), the heating is carried out to a temperature of 90-120°C to ensure that the substances added in step (a) are mixed evenly to form a clear solution.
[0041] Further, in step (b), the water-soluble polymer is one or more of polyvinyl alcohol, carboxymethyl cellulose, gelatin, gum arabic, and sodium polyacrylate.
[0042] Further, in step (b), the Group VIII metal is preferably Ni and / or Co. The nickel source is preferably one or more of basic nickel carbonate, nickel sulfate, and nickel nitrate, and the cobalt source is preferably cobalt nitrate.
[0043] Further, in step (b), the mass concentration of the water-soluble polymer in the aqueous phase obtained in step (b) is 4.0% to 14.0%.
[0044] Further, in step (b), the concentration of Group VIB metals as oxides in the internal aqueous phase is 8-80 g / 100 mL, preferably 10-60 g / 100 mL, the concentration of Group VIII metals as oxides is 2-50 g / 100 mL, preferably 5-30 g / 100 mL, and the concentration of additives as oxides is 0-15.0 g / 100 mL, preferably 0.5-10.0 g / 100 mL.
[0045] Further, in step (c), the mass ratio of the internal aqueous phase to the oil phase is 0.4 to 12.0:1.0, preferably 0.5 to 9.0:1.0.
[0046] Further, in step (c), the oil phase includes a surfactant and oil, wherein the mass ratio of the surfactant to the oil is 1.0:0.1 to 10.0, preferably 1.0:2.0 to 10.0.
[0047] Further, in step (c), the surfactant is selected from glyceryl monostearate, glyceryl distearate, glyceryl monolaurate, and polyoxyethylene ether fatty alcohol (structure R-(OCC)). x -OH, where R is a straight-chain alkyl group with 12 to 15 carbon atoms, and x is 2 to 11) or more of the following: the oil may be at least one of silicone oil and vegetable oil; the silicone oil is selected from at least one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, and methyl phenyl silicone oil; and the vegetable oil is selected from one or more of peanut oil, coconut oil, and tea seed oil.
[0048] Further, in step (c), the oil phase is in a liquid state. The oil phase is maintained at a temperature of 45–85°C, and the stirring rate is 400–800 r / min.
[0049] Further, in step (c), the preparation process of the oil phase includes: adding a surfactant to the oil and heating it to obtain the oil phase. The heating temperature is 45–85°C to make the oil phase present a homogeneous liquid state.
[0050] Furthermore, in step (c), during the dropwise addition of the internal aqueous phase to the oil phase, simultaneous stirring and shear homogenization is performed. Furthermore, the stirring and shear homogenization process involves a stirring speed of 10,000–18,000 rpm, a shear homogenization time of 3–8 min, and a temperature of 50–85°C.
[0051] Further, in step (d), the hydrophilic agent is one or more of polysorbate, sorbitan monolaurate, aluminum monostearate, sodium dioctyl succinate sulfonate, benzyl ammonium chloride, and hexadecanetrimethylamine bromide.
[0052] Further, in step (d), the water is distilled water or deionized water, and the conductivity of the water should be less than 10.0 mS.
[0053] Further, in step (d), the mass concentration of the hydrophilic agent in the external aqueous phase is 5.0% to 20.0%, preferably 6.0% to 18.0%.
[0054] Further, in step (e), the mass ratio of the "internal aqueous phase / oil phase" emulsion to the external aqueous phase is 0.5 to 10.0:1.0, preferably 0.5 to 8.0:1.0.
[0055] A second aspect of the present invention provides a residue oil hydrogenation catalyst prepared by any of the preparation methods described in the first aspect.
[0056] Further, the catalyst includes a catalyst intermediate and a second active metal, wherein the catalyst intermediate includes mesoporous alumina, activated carbon, and a first active metal; the catalyst intermediate includes macropores and mesopores, wherein the pore volume of mesopores with a pore size of 6.0–25.0 nm accounts for 10.0%–34.5% of the total pore volume, preferably 15.0%–29.5%, and the pore volume of macropores with a pore size of 50.0–300.0 nm accounts for 39.5%–50.0% of the total pore volume, preferably 41.5%–48.0%.
[0057] Furthermore, the first active metal is selected from one or more group VIB metals, preferably Mo and / or W; the second active metal includes group VIB metals and group VIII metals, wherein the group VIB metals are preferably Mo and / or W, and the group VIII metals are preferably Ni and / or Co.
[0058] Furthermore, the specific surface area of the mesoporous alumina is 310–500 m² / g. 2 / g, preferably 330-500m 2 / g, with a mesopore size of 11.0–25.0 nm, preferably 12.0–17.0 nm. 2 / g, with a pore volume of 1.10 to 1.5 mL / g, preferably 1.25 to 1.50 mL / g.
[0059] Furthermore, in the mesoporous alumina, the amount of medium-strong acid accounts for more than 55% of the total acid content, preferably 58% to 65%. The total acid content refers to the sum of the amounts of weak acid, medium-strong acid, and strong acid, and the unit of acid content is mmol / g. In the modified mesoporous alumina, the total acid content is 0.230 to 0.265 mmol / g, preferably 0.230 to 0.250 mmol / g.
[0060] Furthermore, in the catalyst, based on the mass of the catalyst, the content of the first active metal as oxide is 10-30%, preferably 10-20%, the content of the second active metal as oxide is 2-10%, preferably 2-6%, and the mass ratio of mesoporous alumina to activated carbon is 1.0-6.0, preferably 1.5-5.0.
[0061] Furthermore, in the catalyst, the mass ratio of the Group VIB metal in the second active metal (calculated as oxide) to the Group VIB metal in the first active metal (calculated as oxide) is 0.4 to 4.0.
[0062] Further, in the catalyst intermediate, the amount of Brønsted acid accounts for 20.0% to 30.0% of the sum of the amounts of Brønsted acid and Lewis acid, preferably 23.0% to 30.0%. In the catalyst, the amount of Brønsted acid is 19.5 to 30.0 μmol / g, preferably 21.0 to 30.0 μmol / g.
[0063] The third aspect of the present invention provides the application of the above-mentioned catalyst in the hydrodemetallization of residue oil.
[0064] Compared with the prior art, the present invention has the following beneficial effects:
[0065] This invention provides a method for preparing a residue oil hydrotreating catalyst. First, a self-assembly method is used, mainly by controlling the alcohol / aluminum molar ratio, the alcohol / template molar ratio, and the introduction method of the template agent. Simultaneously, a bifunctional directing agent is introduced during the self-assembly process, combined with hydrothermal treatment, to prepare mesoporous alumina with more suitable specific surface area, pore structure, and surface acid distribution. Then, based on the above-mentioned mesoporous alumina material, it is mixed with high-temperature activated carbon with macropores and some main active metals (Group VIB metals) to form a hydrotreating catalyst intermediate with more suitable pore distribution and Brønsted acid distribution, providing a foundation for subsequent loading in a multiphase impregnation solution of "internal aqueous phase / oil phase / external aqueous phase". Through comprehensive coordination of each step, the obtained catalyst, when used in the residue oil hydrotreating demetallization reaction, exhibits significantly improved demetallization activity and long-term operating performance. Detailed Implementation
[0066] The technical solutions and effects of the present invention will be further illustrated below with reference to the embodiments, but the invention is not limited to the following embodiments.
[0067] In this invention, the determination of L-acid or Brønsted acid is performed using infrared spectroscopy. The instrument used is a Nicot Fourier Transform Infrared Spectrometer-6700 (USA). The determination method is as follows: The sample to be measured is ground and pressed into a thin sheet with a thickness of approximately 0.1 mm, which is then placed in an infrared cell. The in-situ infrared cell is heated from room temperature to 350 °C over a programmed temperature range of 20 min and held for 120 min, then cooled to 200 °C over a 10 min period. The in-situ cell is then evacuated to a vacuum of 0.01 Pa. The sample is scanned as the background spectrum, and pyridine vapor is used as a probe molecule to scan the sample at 200 °C. The total amount of total acid, Brønsted acid, and L-acid can then be obtained. The units for the amounts of Brønsted acid and L-acid are μmol / g.
[0068] In this invention, the acid content of moderately strong acids was determined using the NH3-TPD method. The instrument used was an Auto-Chem II 2920 chemisorption analyzer from Micron Instruments. Ammonia was used as the adsorption / desorption medium, and helium as the carrier gas. Programmed temperature desorption and chromatographic analysis were employed to obtain the acid content in different desorption temperature ranges. The acid content of weak acids corresponds to an ammonia desorption temperature below 200℃, the acid content of moderately strong acids corresponds to an ammonia desorption temperature of 200℃–400℃, and the acid content of strong acids corresponds to an ammonia desorption temperature above 400℃. The unit of acid content is mmol / g, which represents the amount of ammonia adsorbed per gram of molecular sieve. The sum of the acid content of weak, moderately strong, and strong acids is the total acid content.
[0069] In each example of the present invention, the room temperature is 25°C.
[0070] In various embodiments of the present invention, the molecular weight of the bifunctional structure-directing agent polyethylene glycol-distearatephosphatidylethanolamine is 872.14.
[0071] Example 1
[0072] This example illustrates the preparation method of an "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing a second active metal:
[0073] In this example, the surfactant is glyceryl monostearate, the silicone oil is methyl silicone oil, and the mass ratio of surfactant to silicone oil is 1.0:8.0. The co-emulsifier is polyethylene glycol-8000, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is polyvinyl alcohol (molecular weight 200,000), and the hydrophilic agent is hexadecyltrimethylamine bromide. The mass ratio of co-emulsifier: molybdenum source (calculated as molybdenum oxide): phosphorus source (calculated as phosphorus oxide): nickel source (calculated as nickel oxide): water-soluble polymer: water is 8:26:11:25:18:96. The mass ratio of oil phase to internal aqueous phase is 1.0:0.6. The mass ratio of hydrophilic agent to water is 36:366. The mass ratio of "internal aqueous phase / oil phase" type emulsion to external aqueous phase is 0.7:1.0. The surfactant glyceryl monostearate is added to the silicone oil and heated to 80°C until the silicone oil melts, thus obtaining the oil phase.
[0074] (a) Polyethylene glycol-8000, molybdenum oxide, and phosphoric acid were added to deionized water in sequence. A reflux condenser was used during the reaction. The reaction started at 28°C. During the reaction, the stirring speed was 600 r / min. When the temperature was raised to 100°C, the temperature was maintained for 5 h. The stirring speed was kept constant until a clear solution was obtained.
[0075] (b) First, add basic nickel carbonate to the clear solution obtained in step (a), and then add water-soluble polymer polyvinyl alcohol to obtain an inner aqueous phase;
[0076] (c) The aqueous phase from step (b) is added dropwise to the oil phase. During the addition, the temperature of the oil phase is maintained at 75°C, and the mixture is stirred. The shear homogenization rate is 15000 rpm, the shear homogenization time is 5 min, and the temperature during the shear homogenization process is 70°C. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" emulsion is obtained.
[0077] (d) Add the hydrophilic agent to the water to obtain the external aqueous phase;
[0078] (e) The “inner aqueous phase / oil phase” type emulsion obtained in step (c) is added dropwise to the outer aqueous phase obtained in step (d) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0079] The preparation method of the residue hydrogenation catalyst in this example:
[0080] (1) Add 75g of aluminum isopropoxide and 70mL of nitric acid to 465mL of ethanol and stir at room temperature to perform pre-hydrolysis to obtain a precursor solution; add 35g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain aluminum sol A.
[0081] (2) Add 40g of template agent P123 to 300mL of ethanol and stir at room temperature for 6h to obtain solution B.
[0082] (3) Solution A was added dropwise to B to obtain solution C; 53g of bifunctional structure directing agent polyethylene glycol-distearatephosphatidylethanolamine was prepared with 120mL ethanol and 18mL nitric acid to form solution X. Solution X was added dropwise to solution C and stirred for 2h. The solution was then transferred to a hydrothermal reactor for hydrothermal treatment at 230℃ for 5h. After cooling to room temperature, solution D was obtained. Solution D was placed in an oven at 180℃ and the solvent was allowed to evaporate automatically until the sample was dry. The sample was then calcined in a muffle furnace at 550℃ for 3h to obtain mesoporous alumina.
[0083] (4) The above-obtained mesoporous alumina 296g, high-temperature activated carbon (heat resistance temperature of 800℃, pore volume of 1.6mL / g, and pore volume of 50~300nm accounting for 35% of the total pore volume) 108g, guar gum powder 6g, ammonium heptamolybdate 76g and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 600℃ for 4h to obtain the catalyst intermediate.
[0084] (5) The catalyst intermediate obtained in step (4) is saturated with an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal, and then dried at 120°C for 4 hours and calcined at 550°C for 3 hours to obtain the catalyst.
[0085] Example 2
[0086] This example illustrates the preparation method of an "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing a second active metal:
[0087] In this example, the surfactant is glyceryl monostearate, the silicone oil is methyl silicone oil, and the mass ratio of surfactant to silicone oil is 1.0:4.0. The co-emulsifier is polyethylene glycol-8000, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is polyvinyl alcohol (molecular weight 200,000), and the hydrophilic agent is hexadecyltrimethylamine bromide. The mass ratio of co-emulsifier: molybdenum source (calculated as molybdenum oxide): phosphorus source (calculated as phosphorus oxide): nickel source (calculated as nickel oxide): water-soluble polymer: water is 8:34:15:23:18:286. The mass ratio of oil phase to internal aqueous phase is 1.0:2.0. The mass ratio of hydrophilic agent to water is 16:143. The mass ratio of "internal aqueous phase / oil phase" type emulsion to external aqueous phase is 3.0:1.0. The surfactant glyceryl monostearate is added to the silicone oil and heated to 80°C until the silicone oil melts, thus obtaining the oil phase.
[0088] (a) Polyethylene glycol-8000, molybdenum oxide, and phosphoric acid were added to deionized water in sequence. A reflux condenser was used during the reaction. The reaction started at 28°C. During the reaction, the stirring speed was 600 r / min. When the temperature was raised to 100°C, the temperature was maintained for 5 h. The stirring speed was kept constant until a clear solution was obtained.
[0089] (b) First, add basic nickel carbonate to the clear solution obtained in step (a), and then add water-soluble polymer polyvinyl alcohol to obtain an inner aqueous phase;
[0090] (c) The aqueous phase from step (b) is added dropwise to the oil phase. During the addition, the temperature of the oil phase is maintained at 75°C, and the mixture is stirred. The shear homogenization rate is 15000 rpm, the shear homogenization time is 5 min, and the temperature during the shear homogenization process is 70°C. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" emulsion is obtained.
[0091] (d) Add the hydrophilic agent to the water to obtain the external aqueous phase;
[0092] (e) Add the “internal aqueous phase / oil phase” emulsion obtained in step (c) dropwise to the external aqueous phase obtained in step (d) to obtain an “internal aqueous phase / oil phase / external aqueous phase” impregnation solution.
[0093] The preparation method of the residue hydrogenation catalyst in this example:
[0094] (1) Add 74g of aluminum isopropoxide and 65mL of nitric acid to 358mL of ethanol and stir at room temperature to perform pre-hydrolysis to obtain a precursor solution; add 62g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain aluminum sol A.
[0095] (2) Add 42g of template agent P123 to 328mL of ethanol and stir at room temperature for 6h to obtain solution B.
[0096] (3) Solution A was added dropwise to B to obtain solution C; 62g of bifunctional structure directing agent polyethylene glycol-distearatephosphatidylethanolamine was prepared with 160mL ethanol and 25mL nitric acid to form solution X. Solution X was added dropwise to solution C and stirred for 2h. The solution was then transferred to a hydrothermal reactor for hydrothermal treatment at 210℃ for 6h. After cooling to room temperature, solution D was obtained. Solution D was placed in an oven at 180℃ and the solvent was allowed to evaporate automatically until the sample was dry. The sample was then calcined in a muffle furnace at 550℃ for 3h to obtain mesoporous alumina.
[0097] (4) The above-obtained mesoporous alumina 246g, high-temperature activated carbon (heat resistance temperature of 750℃, pore volume of 1.4mL / g, and pore size of 50~300nm accounting for 30% of the total pore volume) 130g, guar gum powder 8g, ammonium heptamolybdate 60g and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 600℃ for 4h to obtain the catalyst intermediate.
[0098] (5) The catalyst intermediate obtained in step (4) is saturated with an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal, and then dried at 120°C for 4 hours and calcined at 550°C for 3 hours to obtain the catalyst.
[0099] Example 3
[0100] This example illustrates the preparation method of an "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing a second active metal:
[0101] In this example, the surfactant is glyceryl monostearate, the silicone oil is methyl silicone oil, and the mass ratio of surfactant to silicone oil is 1.0:10.0. The co-emulsifier is polyethylene glycol-8000, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is polyvinyl alcohol (molecular weight 200,000), and the hydrophilic agent is hexadecyltrimethylamine bromide. The mass ratio of co-emulsifier: molybdenum source (calculated as molybdenum oxide): phosphorus source (calculated as phosphorus oxide): nickel source (calculated as nickel oxide): water-soluble polymer: water is 8:35:11:25:18:327. The mass ratio of oil phase to internal aqueous phase is 1.0:3.0. The mass ratio of hydrophilic agent to water is 32:174. The mass ratio of "internal aqueous phase / oil phase" type emulsion to external aqueous phase is 2.5:1.0. The surfactant glyceryl monostearate is added to the silicone oil and heated to 80°C until the silicone oil melts, thus obtaining the oil phase.
[0102] (a) Polyethylene glycol-8000, molybdenum oxide, and phosphoric acid were added to deionized water in sequence. A reflux condenser was used during the reaction. The reaction started at 28°C. During the reaction, the stirring speed was 600 r / min. When the temperature was raised to 100°C, the temperature was maintained for 5 h. The stirring speed was kept constant until a clear solution was obtained.
[0103] (b) First, add basic nickel carbonate to the clear solution obtained in step (a), and then add water-soluble polymer polyvinyl alcohol to obtain an inner aqueous phase;
[0104] (c) The aqueous phase from step (b) is added dropwise to the oil phase. During the addition, the temperature of the oil phase is maintained at 75°C, and the mixture is stirred. The shear homogenization rate is 15000 rpm, the shear homogenization time is 5 min, and the temperature during the shear homogenization process is 70°C. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" emulsion is obtained.
[0105] (d) Add the hydrophilic agent to the water to obtain the external aqueous phase;
[0106] (e) The “inner aqueous phase / oil phase” type emulsion obtained in step (c) is added dropwise to the outer aqueous phase obtained in step (d) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0107] The residual oil hydrogenation catalyst in this example was prepared according to the method in Example 1.
[0108] Example 4
[0109] The "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal in this example is the same as in Example 1.
[0110] The preparation method of the residue hydrogenation catalyst in this example:
[0111] (1) Add 48g of aluminum isopropoxide and 66mL of nitric acid to 365mL of ethanol and stir at room temperature to perform pre-hydrolysis to obtain a precursor solution; add 26g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain aluminum sol A.
[0112] (2) Add 26g of template agent P123 to 250mL of ethanol and stir at room temperature for 6h to obtain solution B.
[0113] (3) Solution A was added dropwise to B to obtain solution C; 53g of bifunctional structure directing agent polyethylene glycol-distearatephosphatidylethanolamine was prepared with 150mL ethanol and 25mL nitric acid to form solution X. Solution X was added dropwise to solution C and stirred for 2h. The solution was then transferred to a hydrothermal reactor for hydrothermal treatment at 160℃ for 5h. After cooling to room temperature, solution D was obtained. Solution D was placed in an oven at 180℃ and the solvent was allowed to evaporate automatically until the sample was dry. The sample was then calcined in a muffle furnace at 550℃ for 3h to obtain mesoporous alumina.
[0114] (4) The above-obtained mesoporous alumina 270g, high-temperature activated carbon (heat resistance temperature of 750℃, pore volume of 1.2mL / g, and pore volume of 50~300nm accounting for 25% of the total pore volume) 90g, guar gum powder 6g, ammonium heptamolybdate 74g and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 600℃ for 4h to obtain the catalyst intermediate.
[0115] (5) The catalyst intermediate obtained in step (4) is saturated with an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal, and then dried at 120°C for 4 hours and calcined at 550°C for 3 hours to obtain the catalyst.
[0116] Example 5
[0117] The "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal in this example is the same as in Example 1.
[0118] The preparation method of the residue hydrogenation catalyst in this example:
[0119] (1) Add 45g of aluminum isopropoxide and 54mL of nitric acid to 420mL of ethanol and stir at room temperature to perform pre-hydrolysis to obtain a precursor solution; add 35g of sodium dodecyl sulfate to the precursor solution and continue stirring for 3h to obtain aluminum sol A.
[0120] (2) Add 74g of template agent P123 to 280mL of ethanol and stir at room temperature for 6h to obtain solution B.
[0121] (3) Solution A was added dropwise to B to obtain solution C; 53g of bifunctional structure directing agent polyethylene glycol-distearatephosphatidylethanolamine was prepared with 150mL ethanol and 25mL nitric acid to form solution X. Solution X was added dropwise to solution C and stirred for 2h. The solution was then transferred to a hydrothermal reactor for hydrothermal treatment at 165℃ for 4.5h. After cooling to room temperature, solution D was obtained. Solution D was placed in an oven at 180℃ and the solvent was allowed to evaporate automatically until the sample was dry. The sample was then calcined in a muffle furnace at 550℃ for 3h to obtain mesoporous alumina.
[0122] (4) The above-obtained mesoporous alumina 310g, high-temperature activated carbon (heat resistance temperature of 800℃, pore volume of 1.2mL / g, and pore volume of 50~300nm accounting for 20% of the total pore volume) 90g, guar gum powder 12g, ammonium heptamolybdate 76g and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 600℃ for 4h to obtain the catalyst intermediate.
[0123] (5) The catalyst intermediate obtained in step (4) is saturated with an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal, and then dried at 120°C for 4 hours and calcined at 550°C for 3 hours to obtain the catalyst.
[0124] Comparative Example 1
[0125] Compared with Example 1, the difference is that the mesoporous alumina in this example was prepared according to the method in the literature ("P123 Preparation and Properties of Template Alumina Mesoporous Materials." Journal of Dalian Railway Institute 27.1 (2006): 71-75):
[0126] Weigh 75g of aluminum isopropoxide and dissolve it in 465mL of deionized water. Add 70mL of nitric acid to form a sol. Stir the solution in an 80℃ water bath for 1h. When the solution cools to room temperature, weigh 40g of P123 and dissolve it in the solution. Stir for 1h. Then transfer the solution to a stainless steel autoclave lined with polytetrafluoroethylene for hydrothermal reaction at a filling degree of 70% and a hydrothermal reaction temperature of 100℃ for 24h. After the hydrothermal reaction is completed, let the autoclave cool to room temperature and dry the reaction product in an oven at 60℃. Then calcine it in a muffle furnace at 550℃ for 3h to obtain mesoporous alumina.
[0127] The "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal in this example is the same as in Example 1.
[0128] The catalyst in this example was prepared according to the method in Example 1.
[0129] Comparative Example 2
[0130] Compared with Example 1, the difference lies in the fact that the preparation method of the impregnation solution containing the second active metal in this example includes the following steps:
[0131] In this example, the surfactant is glyceryl monostearate, the silicone oil is methyl silicone oil, and the mass ratio of surfactant to silicone oil is 1.0:8.0. The co-emulsifier is polyethylene glycol-8000, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, and the hydrophilic agent is hexadecyltrimethylamine bromide. The mass ratio of co-emulsifier, molybdenum source (calculated as molybdenum oxide), phosphorus source (calculated as phosphorus oxide), nickel source (calculated as nickel oxide), and water is 8:26:11:25:96. The mass ratio of oil phase to internal aqueous phase is 1.0:0.6. The mass ratio of hydrophilic agent to water is 36:366. The mass ratio of the "internal aqueous phase / oil phase" type emulsion to the external aqueous phase is 0.7:1.0.
[0132] (1) Molybdenum oxide, basic nickel carbonate and phosphoric acid were added to deionized water in sequence. A reflux condenser was used during the reaction. The reaction started at 28°C. During the reaction, the stirring speed was 600 r / min. When the temperature was raised to 100°C, it was maintained for 5 h. The stirring speed was kept constant until a transparent clear solution was obtained, and an internal aqueous phase was obtained.
[0133] (2) Add the hydrophilic agent to the water to obtain the external aqueous phase;
[0134] (3) Add the surfactant glyceryl monostearate, silicone oil, and co-emulsifier polyethylene glycol-8000 to the aqueous phase obtained in step (1) while stirring. The shear homogenization speed is 15000 rpm, the shear homogenization time is 5 min, and the temperature during the shear homogenization process is 70℃. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" type emulsion is obtained.
[0135] (4) Add the “inner aqueous phase / oil phase” emulsion obtained in step (3) to the outer aqueous phase obtained in step (2) to obtain the “inner aqueous phase / oil phase / outer aqueous phase” impregnation solution.
[0136] The catalyst in this example was prepared according to the method in Example 1.
[0137] Compared with Example 1, the hydrogenation catalyst obtained by impregnating the supported catalyst intermediate with an "inner aqueous phase / oil phase / outer aqueous phase" impregnation liquid prepared by the method of Comparative Example 2 could not meet the requirements of long-term operation of the hydrogenation test device, and the relative demetallization rate was only 92.26% after 2000 hours of operation.
[0138] Comparative Example 3
[0139] The preparation method of the "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal in this example is the same as in Example 1.
[0140] The preparation steps (1), (2), (3), and (5) of the hydrogenation catalyst in this example are the same as in Example 1, except that high-temperature activated carbon is not introduced in step (4).
[0141] (4) The above-obtained mesoporous alumina 404g, guar gum powder 6g, ammonium heptamolybdate 76g and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 600℃ for 4h to obtain the catalyst intermediate.
[0142] Comparative Example 4
[0143] The preparation steps (1), (2), (3), and (4) of the hydrogenation catalyst in this example are the same as those in Example 1. The difference is that in step (5), the supported catalyst intermediate is impregnated with a conventional Mo-Ni-P impregnation solution, wherein the content of molybdenum, nickel, and phosphorus in the impregnation solution is the same as that in the impregnation solution of Example 1.
[0144] (5) Prepare a Mo-Ni-P impregnation solution by taking molybdenum oxide, basic nickel carbonate, phosphoric acid and deionized water, and then saturate the catalyst intermediate obtained in step (4) with it. After drying at 120°C for 6 hours and calcining at 600°C for 4 hours, the catalyst is obtained.
[0145] Comparative Example 5
[0146] The preparation steps (1), (2), and (3) of the hydrogenation catalyst in this example are the same as those in Example 1. The difference is that the active metal molybdenum is not introduced in step (4), and the mass of MoO3 introduced into the catalyst by the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation liquid in step (5) is 100% of the total MoO3 loading in the catalyst.
[0147] (4) The above-obtained mesoporous alumina 296g, high-temperature activated carbon (heat resistance temperature of 800℃, pore volume of 1.6mL / g, and pore volume of 50~300nm accounting for 35% of the total pore volume) 108g, guar gum powder 6g and deionized water were extruded into strips, dried at 120℃ for 6h and calcined at 600℃ for 4h to obtain the catalyst intermediate;
[0148] (5) Prepare an impregnation solution of “internal aqueous phase / oil phase / external aqueous phase”, then saturate the catalyst intermediate obtained in step (4), and dry it at 120°C for 6 hours and calcine it at 600°C for 4 hours to obtain the catalyst.
[0149] Table 1. Properties of the mesoporous alumina obtained in each example.
[0150]
[0151] Table 2 shows the composition of the catalysts obtained in each example.
[0152]
[0153] Table 3. Properties of the catalyst intermediates obtained in each example.
[0154]
[0155]
[0156] Note: *The percentage (%) of the amount of Brønsted acid to the sum of the amounts of Brønsted acid and L-acid in the obtained catalyst intermediate is represented by A;
[0157] **In the obtained catalyst intermediate, the proportion (%) of mesopores with a pore size of 6.0–25.0 nm to the total pore volume is represented by B; the proportion (%) of macropores with a pore size of 50.0–300.0 nm to the total pore volume is represented by C.
[0158] Evaluation test
[0159] Activity stability tests were conducted on Examples 1-5 and Comparative Examples 1-5 using a 200mL fixed-bed hydrogenation test apparatus. The feedstock was residue oil with a density of 975.9 kg / m³. 3 (20℃), S content 2.73wt%, Ni and V contents 28.2μg / g and 62.8μg / g respectively, CCR content 12.7wt%, the demetallization rate after 2000h of operation in Example 1 was 100%, and all others were relative demetallization rates. Specific experimental conditions are shown in Table 4, and experimental results are shown in Tables 5 and 6.
[0160] Table 4 Test Conditions
[0161] Reaction temperature, °C 370 Reaction pressure, MPa 15.7 <![CDATA[Liquid hourly space velocity, h -1 > 1.0 Hydrogen-to-oil ratio, V / V 750
[0162] Table 5. Test results of the hydrogenation demetallization catalysts in each example.
[0163]
[0164] Table 6. Experimental results of hydrogenation demetallization catalysts in each comparative example.
[0165] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Relative demetallization rate, % 91.42 92.26 91.73 91.81 92.03
[0166] The specific embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A method for preparing a residue oil hydrotreating catalyst, comprising the following steps: (0) Preparation of an impregnation solution containing a second active metal: First, the inner aqueous phase containing the second active metal is added dropwise to the oil phase to obtain an "inner aqueous phase / oil phase" type emulsion; then it is added dropwise to the outer aqueous phase to obtain an impregnation solution containing the second active metal. (1) Aluminum sol A, alcoholic solution of template agent B and mixture X containing bifunctional structure directing agent are mixed, subjected to hydrothermal treatment, dried and calcined to obtain mesoporous alumina; (2) The mesoporous alumina, activated carbon, first active metal source and molding aid obtained in step (1) are mixed and shaped, dried and calcined to obtain a catalyst intermediate; (3) Impregnate the catalyst intermediate obtained in step (2) with an impregnation solution containing a second active metal, dry and calcine to obtain the catalyst.
2. The preparation method according to claim 1, characterized in that, In step (1), the preparation process of aluminum sol A is as follows: aluminum source, acid and alcohol are mixed and pre-hydrolyzed to obtain aluminum sol A; Preferably, the aluminum source is one or more of aluminum nitrate, aluminum chloride, and aluminum isopropoxide; the acid is an inorganic acid, preferably one or more of sulfuric acid, nitric acid, and hydrochloric acid; and the alcohol is a low-carbon alcohol, preferably one or more of ethanol, propanol, and butanol. And / or, the pre-hydrolysis temperature is 20–60°C, and the pre-hydrolysis time is 1–12 h; And / or, in step (1), the ethanol / aluminum molar ratio is 10.0 to 80.0, preferably 10.0 to 45.0; And / or, in step (1), the acid / aluminum molar ratio is 1.0 to 12.0, preferably 1.0 to 5.
0.
3. The preparation method according to claim 1, characterized in that, In step (1), the aluminum source, acid and alcohol are first mixed and pre-hydrolyzed to obtain a precursor solution. Then, an ionic emulsifier is added dropwise to the precursor solution to obtain aluminum sol A. And / or, the ionic emulsifier is one or more of sodium dodecyl sulfate and fatty polyoxyethylene ether sulfate salt; Preferably, the amount of ionic emulsifier added is related to the amount of precursor solution used in a ratio of 0 to 18 g / 100 mL, and more preferably 5 to 15 g / 100 mL.
4. The preparation method according to claim 1, characterized in that, In step (2), the template agent in the alcohol solution B is at least one of P123, SDBS and AOT, preferably P123; preferably, the molar ratio of alcohol to template agent is 300 to 1000. And / or, in step (1), the molar ratio of aluminum source to template agent in aluminum sol A is 50 to 200.
5. The preparation method according to claim 1, characterized in that, In step (1), the mixture X comprises a bifunctional structure directing agent, an alcohol, and an acid, wherein the bifunctional structure directing agent is polyethylene glycol-distearatephosphatidylethanolamine, the alcohol is preferably ethanol, and the acid is preferably nitric acid; And / or, in the mixture X, the mass ratio of the bifunctional directed agent to the sum of the volumes of the alcohol and acid is 0.05–0.85 g / mL, preferably 0.30–0.75 g / mL; and / or, in the mixture X, the volume ratio of the alcohol to the acid is 4–12; And / or, the ratio of the molar amount of the bifunctional structure directing agent to the sum of the molar amounts of the bifunctional structure directing agent and the aluminum source in solution A is 0.1 to 0.5; And / or, in step (3), the conditions for the hydrothermal treatment are: temperature 160-280℃, preferably 180-260℃, time 3-12h, preferably 4-8h; And / or, in step (3), the calcination temperature is 500-650°C and the calcination time is 3-8h.
6. The preparation method according to claim 1, characterized in that, In step (2), the activated carbon is a high-temperature activated carbon with a minimum heat resistance temperature of not less than 700°C, preferably 750-800°C; And / or, the activated carbon has a pore volume of 1.0 to 1.8 mL / g, and the pore volume of pores with a diameter of 50.0 to 300.0 nm accounts for 15% to 35% of the total pore volume.
7. The preparation method according to claim 1, characterized in that, In step (2), the molding aid is one or more of guar gum powder and methylcellulose; Preferably, the molding aid is added at a mass ratio of 1.0% to 8.0% of the total mass of mesoporous alumina and activated carbon.
8. The preparation method according to claim 1, characterized in that, In step (2), the first active metal is one or more of the group VIB metals, preferably Mo and / or W; Preferably, the mass of the first active metal source, calculated as oxides, is 8% to 18% of the total mass of mesoporous alumina and activated carbon.
9. The preparation method according to claim 1, characterized in that, In step (2), the drying temperature is 120-200℃ and the drying time is 4-10h; And / or, the calcination temperature is 500–650°C, and the calcination time is 3–8 hours.
10. The preparation method according to claim 1, characterized in that, The method for preparing the impregnation solution containing the second active metal includes: (a) Mix the co-emulsifier, the VIB metal source, water, and optional auxiliary source, and heat to obtain a clear solution; (b) The group VIII metal source, the water-soluble polymer, and the clear solution obtained in step (a) are mixed to obtain the inner aqueous phase; (c) The aqueous phase from step (b) is added dropwise to the oil phase to obtain an "aqueous phase / oil phase" emulsion. (d) Mix the hydrophilic agent and water to obtain the external aqueous phase; (e) The "inner aqueous phase / oil phase" emulsion obtained in step (c) is added dropwise to the outer aqueous phase obtained in step (d) to obtain an impregnation solution containing the second active metal.
11. The preparation method according to claim 10, characterized in that, In step (a), the co-emulsifier is selected from one or more of polyethylene glycol-8000, polyethylene glycol-400, cetyl alcohol, octadecanol, propylene glycol, n-butanol and glycerin; And / or, in step (b), the water-soluble polymer is one or more of polyvinyl alcohol, carboxymethyl cellulose, gelatin, gum arabic, and sodium polyacrylate; And / or, in step (a), the Group VIB metal is Mo and / or W, and the Group VIII metal is Ni and / or Co; And / or, in step (a), the auxiliary agent is selected from at least one of phosphorus, silicon or boron, preferably phosphorus; And / or, in step (d), the hydrophilic agent is one or more of polysorbate, sorbitan monolaurate, aluminum monostearate, sodium dioctyl succinate sulfonate, benzyl ammonium chloride, and hexadecanetrimethylamine bromide.
12. The preparation method according to claim 10, characterized in that, In the internal aqueous phase, the mass concentration of water-soluble polymer is 4.0% to 14.0%; And / or, in the internal aqueous phase, the mass concentration of the co-emulsifier is 0.5% to 5.0%; And / or, in the internal aqueous phase, the concentration of the additive, calculated as oxide, is 0–12.0 g / 100 mL, preferably 0.5–12.0 g / 100 mL; And / or, in the internal aqueous phase, the concentration of Group VIB metals as oxides is 8-80 g / 100 mL, preferably 10-60 g / 100 mL; And / or, in the external aqueous phase, the concentration of Group VIII metals as oxides is 2 to 50 g / 100 mL, preferably 5 to 30 g / 100 mL; And / or, in the external aqueous phase, the mass concentration of the hydrophilic agent is 5.0% to 15.0%.
13. The preparation method according to claim 10, characterized in that, In step (c), the oil phase includes a surfactant and oil; And / or, the surfactant is selected from one or more of glyceryl monostearate, glyceryl distearate, glyceryl monolaurate, and polyoxyethylene ether fatty alcohol; And / or, the oil is selected from at least one of silicone oil and vegetable oil, the silicone oil is selected from at least one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, and methyl phenyl silicone oil, and the vegetable oil is selected from one or more of peanut oil, coconut oil, and tea seed oil.
14. The preparation method according to claim 10 or 13, characterized in that, In the oil phase, the mass ratio of surfactant to oil is 1.0:0.1 to 10.0, preferably 1.0:2.0 to 10.0; And / or, the mass ratio of the internal aqueous phase to the oil phase is 0.4 to 12.0:1.0, preferably 0.5 to 9.0:1.0; And / or, the mass ratio of the "internal aqueous phase / oil phase" type emulsion to the external aqueous phase is 0.5 to 10.0:1.0, preferably 0.5 to 8.0:1.
0.
15. The preparation method according to claim 10, characterized in that, In step (a), the heating temperature is 90–120°C; And / or, in step (c), during the process of adding the internal aqueous phase to the oil phase, stirring and shearing homogenization are carried out simultaneously; preferably, the stirring and shearing homogenization process is carried out at a stirring speed of 10,000 to 18,000 rpm, a homogenization time of 3 to 8 min, and a homogenization temperature of 50 to 85°C.
16. The preparation method according to claim 10, characterized in that, In step (c), the oil phase is in a liquid state; preferably, the oil phase is kept in a liquid state at a temperature of 45–85°C.
17. The residue hydrogenation catalyst prepared by any one of the methods described in claims 1-16.
18. The hydrogenation catalyst according to claim 17, characterized in that, The catalyst comprises a catalyst intermediate and a second active metal, wherein the catalyst intermediate comprises mesoporous alumina, activated carbon, and a first active metal; the catalyst intermediate comprises macropores and mesopores, wherein the pore volume of mesopores with a pore size of 6.0–25.0 nm accounts for 10.0%–34.5% of the total pore volume, preferably 15.0%–29.5%, and the pore volume of macropores with a pore size of 50.0–300.0 nm accounts for 39.5%–50.0% of the total pore volume, preferably 41.5%–48.0%.
19. The hydrogenation catalyst according to claim 18, characterized in that, The mesoporous alumina has a specific surface area of 310–500 m² / g, preferably 330–500 m² / g. 2 / g, with a mesopore size of 11.0–25.0 nm, preferably 12.0–17.0 nm. 2 / g, with a pore volume of 1.10–1.5 mL / g, preferably 1.25–1.50 mL / g; And / or, in the mesoporous alumina, the amount of medium-strong acid accounts for more than 55% of the total acid content, preferably 58% to 65%.
20. The hydrogenation catalyst according to claim 18, characterized in that, In the catalyst intermediate, the amount of Brønsted acid accounts for 20.0% to 30.0% of the sum of the amounts of Brønsted acid and Lewis acid, preferably 23.0% to 30.0%.
21. The hydrogenation catalyst according to claim 18, characterized in that, In the catalyst, based on the mass of the catalyst, the content of the first active metal, calculated as oxide, is 10-30%, preferably 10-20%, and the content of the second active metal, calculated as oxide, is 2-10%, preferably 2-6%. And / or, in the catalyst, the mass ratio of the Group VIB metal in the second active metal (calculated as oxide) to the Group VIB metal in the first active metal (calculated as oxide) is 0.1 to 4.
0. And / or, the mass ratio of mesoporous alumina to activated carbon is 1.0 to 6.0, preferably 1.5 to 5.
0.
22. The application of the hydrogenation catalyst prepared by any of the methods described in claims 1-15 or any of the hydrogenation catalysts described in claims 16-21 in the hydrodemetallization of residue oil.
Citation Information
Patent Citations
Highly thermostable and ordered mesoporous alumina material and preparation method thereof
CN103539173A
